GAME EDUKASI “PERJALANAN SI KOKO” SEBAGAI MEDIA PEMBELAJARAN - Hellyana, Corie Mei; Fadlilah, Nuzul Imam; wijianto, ragil; Ade Putra, Khoerul Amin (Informatics and Computer Engineering Journal, 2023)
Learning the introduction of computer device for children is will very monotonous. Of course, this is not effective and efficient in the learning of children who tend to see something that attracts attention. In addition, very few elements that help learning include images and text. In teaching and learning activities, the learning method is the key to the success of the learning activities carried out. The method used in this research is by means of observation and literature study where researchers make direct observations and study, research and examine various literatures related to the subject related to the background of this educational game. Therefore, the game “Si Koko’s journey” was made as a learning medium which is a game with an educational concept and makes the game fun learning medium. Games are on of the entertainment media that are currently favored by children and adults as mere pleasure, but it would be better if games were created as learning tool so that children can be more creative in thinking. Games that have educational values are better known as educational games. This educational type game aims to provoke interest in learning about the subject matter while playing, so that feelings of pleasure arise in the hope that children can more easily understand the subject matter provided.